The The Impact of COVID-19 Pandemic on Cognitive Function in Older Adults with Dementia: A Systematic Review - Rensa Rensa; Stefania Rosalyn; Alius Cahyadi (International Journal of Biomedical Science and Travel Medicine, 2025)
Background: The prevalence of dementia rises with the increasing life expectancy and elderly population. Due to the COVID-19 pandemic, it is challenging for caregivers to help carry out their daily activities and provide cognitive stimulants to slow down the deterioration. Therefore, this research aims to determine the impact of the COVID-19 pandemic on cognitive function in older people with dementia. Methods: This systematic review sought and reviewed observational studies data taken from various databases such as PubMed, EBSCOHost, Google Scholar, and ScienceDirect starting from January to November 2022—using COVID-19, dementia, cognitive function, and elderly along with their synonyms as keywords. Results: As many as 11 literatures with a total of 3132 participants were obtained to be reviewed. Ten out of 11 pieces of literature showed a deterioration in the cognitive function of older people with dementia due to the COVID-19 pandemic. In comparison, one piece of literature showed an improvement in cognitive function that was not significant. Conclusion: The cognitive function of older people with dementia appears to deteriorate when compared between before and after the COVID-19 pandemic. This can be seen as a decrease in MMSE, MoCA, or both scoring results. However, due to confounding variables not being accounted for in the pieces of literature reviewed, it is impossible to pinpoint the Covid-19 pandemic as the exact reason for this deterioration.